Oil Rents and Fiscal Balance in Oil Dependent Economies: Do Fiscal Rules Matter? - Fatai, Adedoyin Festus; Cheol, Liu; A, Adeniyi Oluwatosin; Muhammad, Kabir (Asian Journal of Empirical Research, 2017)
In this paper, we utilize a panel of oil dependent economies from 2000 to 2015 and attempt to empirically examine the relationship between crude oil rents and fiscal balance, while controlling for other covariates. Our strategy is to highlight the importance of fiscal rules by using an instrumental variable approach based on Dynamic Panel estimators [the General Method of Moment (GMM)]. This is used in comparison with estimations from pooled OLS, LSDV fixed effects, and the IV/2SLS techniques (using each country’s share of world output as instrument). Our pre-estimation diagnostics showed that the GMM approach might not be applicable to the small sample, and we suspected that the IV/2SLS method might also be weak in testing our hypothesis for the oil dependent economies; therefore we maintained the LSDV Fixed effects estimations. Our estimation results shows that in countries with fiscal rules, there is insignificant reaction of fiscal balance to changes in oil rents shocks, and the impact is weak. We find also that welfare spending, which was captured by the real GDP per capita, affects fiscal balance, and so does the budgetary variable, i.e. debt-to-GDP ratio, and the ability of the government to curb corruption and mismanagement of funds, which is politically motivated.